Vitamin D and Its Role in Child Development : A Narrative Review - Paramitha, Fiona; Handoko, Rizki Ekaputra; Cahya, Dini Aulia (Journal of Unified Multidisciplinary Practice in Sports, Health, and Medicine, 2026)
Background: Vitamin D is a crucial prohormone involved in calcium and phosphorus metabolism, with additional neuroprotective, immune-regulatory, and anti-inflammatory functions. Maternal and early-life Vitamin D levels are increasingly recognized as essential for neurocognitive, motor, social-emotional, and behavioral development in children. Objective: This narrative review explores current literature on the impact of Vitamin D on child development, focusing on neurocognitive function, motor skills, social-emotional development, and behavioral outcomes. Methods: Relevant articles were identified through an unsystematic search of PubMed, Scopus, and Google Scholar databases, focusing on studies published in the past decade that discuss vitamin D and its relation to neurodevelopmental outcomes. Results: Maternal Vitamin D insufficiency is associated with delayed language development and lower IQ. Deficiency disrupts dopamine regulation, impairing gross and fine motor skills. Low Vitamin D levels increase the risk of ASD and ADHD. Supplementation studies suggest potential benefits in improving neurodevelopmental and behavioral outcomes. Conclusion: Vitamin D is vital for child development beyond bone health. Ensuring adequate maternal and early-life Vitamin D levels is essential for optimal neurodevelopment and mental health. Public health strategies, including maternal supplementation and dietary interventions, should be prioritized to prevent adverse developmental outcomes linked to Vitamin D deficiency.